Learning across distances: an international collaborative learning project between Berlin and Turku. Issue 2 (3rd April 2019) - Hautala, Johanna; Schmidt, Suntje
ABSTRACT: Many geographers graduating from universities enter an international and project-based professional life, which includes working in geographically dispersed project teams. In Europe, the Bologna process aligned study programs and supported student mobility to prepare students for such a work environment. However, research on higher education has reported few examples of international courses that include collaborative learning during which students have experience of both co-location and geographical dispersion. This paper reports on a pilot course that implemented international student-led research projects in two Geography Departments: the Humboldt-Universität zu Berlin and the University of Turku. We monitored the students' learning processes via a survey that was administered at the beginning, middle and end of the course, complemented by observations, informal discussions and student team reports. We analysed the survey and observations within a proximity-distance framework to identify the key challenges and good practices for supporting collaborative learning. We developed a model for organising an international course that applies both geographical distance and co-location.